2017
DOI: 10.2147/ndt.s148073
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of circulating B- and T-lymphocytes as indicators for stroke outcomes

Abstract: BackgroundStroke has high mortality and morbidity. Biomarkers are required for to predict stroke outcomes, which could help clinicians to provide rationale approaches for patient management. The dynamic changes in circulating immune cells have been reported in stroke patients and animal models of stroke.AimThe aim of this study was to explore biomarkers to predict stroke outcomes by investigating the relationship between the frequencies of circulating immune cells and stroke outcomes.MethodsIn all, 50 acute is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…The reduction in number and functions of circulating lymphocytes was also associated with the lower mortality and better outcome of experimental stroke (Chu et al., 2014; Hurn et al., 2007; Schwartz & Moalem, 2001). However, clinical research on this issue has yielded conflicting results (Noh et al., 2018; Vogelgesang et al., 2008; Wang et al., 2017; Yan et al., 2009). Some research has indicated that a profound infiltration of inflammatory cells (monocytes, macrophages, B lymphocytes, Ts cells, and NK cells) occurs in the brain early after focal ischemia (3 hr after stroke), especially without reperfusion(Gendron et al., 2002), while others showed that the percentages of activated T cells and regulatory T cells were significantly increased in patients with ischemic stroke compared to healthy subjects(Yan et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in number and functions of circulating lymphocytes was also associated with the lower mortality and better outcome of experimental stroke (Chu et al., 2014; Hurn et al., 2007; Schwartz & Moalem, 2001). However, clinical research on this issue has yielded conflicting results (Noh et al., 2018; Vogelgesang et al., 2008; Wang et al., 2017; Yan et al., 2009). Some research has indicated that a profound infiltration of inflammatory cells (monocytes, macrophages, B lymphocytes, Ts cells, and NK cells) occurs in the brain early after focal ischemia (3 hr after stroke), especially without reperfusion(Gendron et al., 2002), while others showed that the percentages of activated T cells and regulatory T cells were significantly increased in patients with ischemic stroke compared to healthy subjects(Yan et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke-induced immunodepression may contribute to the decrease in peripheral lymphocytes and reduce inflammatory-mediated cerebral damage by attenuating over activation of the inflammatory cascade. Therefore, immunodepression post-stroke inversely increases susceptibility to infection and is detrimental to clinical outcomes [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…9,90 The observation of acute lymphopenia and the association between lymphopenia, initial stroke severity, subsequent infection risk, and poor outcome are consistent across ischemic stroke and ICH. 9,90,102–104…”
Section: Peripheral Immune System Response In Hemorrhagic Stroke Outcmentioning
confidence: 99%
“…of acute lymphopenia and the association between lymphopenia, initial stroke severity, subsequent infection risk, and poor outcome are consistent across ischemic stroke and ICH. 9,90,[102][103][104] In SAH, few studies reported on changes in lymphocyte subpopulation. They consistently demonstrated significant decrease in circulating T lymphocytes during acute phase SAH.…”
Section: Sah Cases Prospectivementioning
confidence: 99%